Teori Negosiasi Wajah Dalam Komunikasi Pasangan Untuk Penyelesaian Konflik Di Pengadilan Agama Medan Kelas 1A - Ahmad Yasin; Hasan Sazali (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
Unavoidable marital conflict requires effective communication management to maintain harmonious family ties. This qualitative case study research analyzes the application of Face Negotiation Theory in communication with couples resolving conflicts at the Medan Class 1A Religious Court. Data were collected through in-depth interviews with three subjects (husband/wife) and divorce file documentation. The results show that preventive and restorative face-work plays a crucial role in managing conflict, influenced by cultural assumptions (individualism/collectivism) and personality tendencies (independent/interdependent), as well as situational factors such as role assessment and relational distance. In the formal context that has reached the trial, individuals have specifically experienced a face-threatening process, so that the tendency of mutual-face concern becomes dominant towards self-face concern with the aim of restoring reputation and winning arguments. This study confirms the relevance of Face Negotiation Theory in the communication process with couples for conflict resolution in the religious court environment, offering benefits to increase the effectiveness of mediation and family dispute resolution with attention to the "face" aspect and interpersonal communication behavior.